Activation of a Non‐Heme FeIII‐OOH by a Second FeIII to Hydroxylate Strong C−H Bonds: Possible Implications for Soluble Methane Monooxygenase. Issue 25 (9th May 2019) - Kal, Subhasree; Que, Lawrence
Abstract: Non‐heme iron oxygenases contain either monoiron or diiron active sites, and the role of the second iron in the latter enzymes is a topic of particular interest, especially for soluble methane monooxygenase (sMMO). Herein we report the activation of a non‐heme Fe III ‐OOH intermediate in a synthetic monoiron system using Fe III (OTf)3 to form a high‐valent oxidant capable of effecting cyclohexane and benzene hydroxylation within seconds at −40 °C. Our results show that the second iron acts as a Lewis acid to activate the iron–hydroperoxo intermediate, leading to the formation of a powerful Fe V =O oxidant—a possible role for the second iron in sMMO. Abstract : Lewis acidic Fe III activates Fe III ‐OOH : A mononuclear non‐heme Fe III ‐OOH species can be activated by Lewis acidic Fe III (OTf)3 to form a potent oxidant that can hydroxylate cyclohexane and benzene within seconds at −40 °C. These observations provide useful insight into the chemistry required for the diiron enzyme sMMO in its conversion of methane to methanol.